An Integrated Blockchain Framework for Secure Autonomous Vehicle Communication System - Juan de Anda-Suárez; José Luis López-Ramírez; Daniel Jimenez-Mendoza; José Manuel Benitez-Quintero; Eli Gabriel Avina-Bravo; David Asael Gutierrez-Hernandez; Juan Gabriel Avina-Cervantes (Information, 2025)
Autonomous Vehicles (AV) have been extensively studied in both scientific and social contexts. Over the past two decades, there has been a significant rise in their real-world applications, including neural networks, Blockchain, Internet of Things, autonomous navigation, computer vision, automation processes, and various other areas. Hence, it is imperative to investigate the interplay between software, hardware, and individuals. To guarantee secure and unaffected interactions within autonomous vehicle devices and networks, decentralized Blockchain technology is proposed. This study presents the introduction of a framework we named “DEMU-NAV” for an ecosystem that includes Artificial Intelligence (AI), humans, and robots. The framework makes use of a decentralized Blockchain, Smart-Contract (SC), and Internet of things (IoT) network. Our framework was implemented using Ethereum and Python, enabling us to oversee Blockchain, Smart-Contracts, and the IoT for the facilitation of autonomous vehicle navigation.